Perceptions, Attitude, Responses, Knowledge and Emotional Well-being (PARKE) of COVID-19 among students at Newcastle University Medicine Malaysia (NUMed) - Joyce Chzi Ching Chee; Sylvia Wei Wei Kong; Zhi Jing Tan; Yi Khai Lim; Mark S Pearce; Edmund L C Ong (Journal of Global Health Reports)
# Background